2019
DOI: 10.1111/sed.12659
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy and geochemistry of atypical reduction spheroids from the Tumblagooda Sandstone, Western Australia

Abstract: High resolution X-ray computed tomography and its application to ore deposits: from data acquisition to quantitative three-dimensional measurements with case studies from Ni-Cu-PGE deposits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
(78 reference statements)
0
0
0
Order By: Relevance
“…Many researchers refer to such light bands as secondary reduction zones [7]. Geologists have been observing secondary reduction zones for almost as long as the color has been discussed in the literature [32,[72][73][74][75]. According to the mineralogical characteristics and geochemical properties of secondary reduction zones in red beds, two categories have been identified: leaching zones and reduction zones.…”
Section: Reduction and Leachingmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers refer to such light bands as secondary reduction zones [7]. Geologists have been observing secondary reduction zones for almost as long as the color has been discussed in the literature [32,[72][73][74][75]. According to the mineralogical characteristics and geochemical properties of secondary reduction zones in red beds, two categories have been identified: leaching zones and reduction zones.…”
Section: Reduction and Leachingmentioning
confidence: 99%
“…Some researchers have suggested that the higher concentration of metallic elements such as copper in the reduction spots may be due to adsorption by organic matter [76][77][78]. More researchers have suggested that the formation of reduction spots containing dark cores is better attributed to the activity of bacteria or microorganisms that use organic matter as an energy source and reducing agent, allowing the dissolution of metallic elements and their precipitation in the cores of the reduction spots through bacterial-mediated reduction [74,75,81,[83][84][85].…”
Section: Reduction Spotsmentioning
confidence: 99%